Pengaruh Produk Bank Syariah Terhadap Minat Menabung Dengan Persepsi Masyarakat Sebagai Variabel Moderating - Nur Leli; Chuzaimah Batubara (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine Islamic bank products on the interest in saving by using public perceptions as moderating. The research method used is quantitative descriptive, the population is customers of Islamic Commercial Banks (BRI Syariah, BNI Syariah, Mandiri Syariah, Bank Jateng Syariah, Bank Muamalat) located in the Kota Medan sub-district. The research sample is people who make transactions at Islamic Commercial Banks, totaling 100 respondents using the quota sampling technique. The analytical method uses the MRA (Moderating Regression Analysis) test. The results of the study show that the products of Islamic banks in financial institutions have an impact on society, this proves that the products (savings) of microfinance institutions have benefits for customers or the community. While public perception can be a moderating variable, because Commercial Banks are able to provide education to the public that their products are free from elements of usury.